Multifocal capillary malformations in an older, asymptomatic child with a novel RASA1 mutation. (1st March 2016) - Whitaker, S.; Leech, S.; Taylor, A.; Splitt, M.; Natarajan, S.; Rajan, N.
Summary: Multifocal capillary malformation (CM) is the cardinal feature of patients with RASA1 mutations. These CMs are 'red flags', signalling the possible association with an arteriovenous malformation (AVM) or an arteriovenous fistula (AVF). We report an 8‐year‐old boy who presented with > 20 CMs, who was found to have a novel mutation in the RASA1 gene. Radiological screening of children with RASA1 mutations is not standardized, and we elected to carry out baseline magnetic resonance imaging of the brain and spine in our case, which gave normal results. We discuss the recent literature and our approach in the management of such a case.